Comparative Survival Assessment of Two-Dimension (2D) vs Three-Dimension (3D) Brachytherapy Treatment in Cervical Cancer: A Retrospective Case Control Study - Pitchaya Sakyanun (Journal of Radiation and Nuclear Medicine, 2020)
Purpose The purpose of this study was to assess the efficacy (overall survival, local control, progression free survival (PFS) and toxicities between two dimension (2D) and three dimension (3D) CT guided brachytherapy without using interstitial needles in cervical cancer patients. Material and Methods A retrospective case-control study was performed in Figo stage IB-IVA cervical cancer patients treated between March 1990 and August 2018. Concurrent chemoradiation using external beam radiotherapy followed by brachytherapy (BT) was the treatment method used in all patients. Clinical endpoints were overall survival, local control, progression free survival, acute toxicities and late toxicities. Results A 102 cervical cancer patients were included,52 patients have been treated with 2D and 50 patients with 3D using CT scan brachytherapy without interstitial needles. Baseline characteristics were similar between both groups. External beam was used in all patients during concurrent chemoradiation period before brachytherapy. All patients completed the treatment. Similar 3-year overall survival and local control was reported between 2D and 3D techniques. Overall 3-year survival rate was 95.7% in 2D and 91.8% in 3D brachytherapy (P value = 0.188). Local control at the 3 year follow up was 88.6% in 2D and 93.3% in 3D (P value = 0.571). Progression free survival was better in 2D rather than 3D (86.13% in 2D vs 27.4% in 3D, p value = 0.006). No grade 3 or 4 toxicity in 3D technique was observed whereas there are 1.9% of grade 3 acute GI toxicity and grade 3 late GI and GU toxicities in 2D technique (7.7% and 5.8 %). The 3D brachytherapy significantly reduced acute grade 2-3 GI side effect and grade 2-3 late GU side effect (acute GI 25% in 2D vs 4% in 3D, late GU (56% in 2D vs 16% in 3D). Conclusion Using CT guided 3D brachytherapy in treatment of cervical cancer showed similar outcomes in survival and local control but reduced toxicity compared to the 2D technique. Disease progression including metastasis was found better in the 2D brachytherapy technique. CT guided brachytherapy helped reduce dose to organs at risk and long term follow up for survival outcome and toxicities was needed.
Keywords: Cervical Cancer